Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2017)
A dataset containing 24869 species occurrences available in GBIF matching the query: { "and" : [ { "or" : [ "TaxonKey is Oenothera subterminalis R.R.Gates", "TaxonKey is Parthenocissus quinquefolia (L.) Planch.", "TaxonKey is Oxyura jamaicensis (J.F.Gmelin, 1789)", "TaxonKey is Ludwigia perennis L.", "TaxonKey is Parthenocissus vitacea (Knerr) Hitchc.", "TaxonKey is Vallisneria spiralis L.", "TaxonKey is Parthenium hysterophorus L.", "TaxonKey is Oenothera ×nuda Renner ex Rostanski", "TaxonKey is Sagittaria latifolia Willd.", "TaxonKey is Pseudorasbora parva (Temminck & Schlegel, 1846)", "TaxonKey is Spiraea ×pseudosalicifolia Silverside", "TaxonKey is Oenothera speciosa Nutt.", "TaxonKey is Nyctereutes procyonoides (Gray, 1834)", "TaxonKey is Oenothera perangusta R.R.Gates", "TaxonKey is Solanum eleagnifolium Cav.", "TaxonKey is Oenothera glazioviana Micheli", "TaxonKey is Sargassum muticum (Yendo) Fensholt", "TaxonKey is Oenothera indecora Cambess.", "TaxonKey is Oenothera ×paradoxa Hudziok", "TaxonKey is Oenothera victorini R.R.Gates & Catches., 1933", "TaxonKey is Rapana venosa (Valenciennes, 1846)", "TaxonKey is Oenothera ×rubricauloides Rostanski", "TaxonKey is Oenothera ×fallax Renner", "TaxonKey is Spartina ×townsendii H.Groves & J.Groves", "TaxonKey is Sarracenia purpurea L.", "TaxonKey is Spartina pectinata Bosc ex Link", "TaxonKey is Pacifastacus leniusculus (Dana, 1852)", "TaxonKey is Orconectes limosus (Rafinesque, 1817)", "TaxonKey is Oenothera angustissima R.R.Gates", "TaxonKey is Oenothera pycnocarpa G.F.Atk. & Bartlett", "TaxonKey is Oenothera biennis L.", "TaxonKey is Oenothera affinis Cambess.", "TaxonKey is Procyon lotor (Linnaeus, 1758)", "TaxonKey is Myriophyllum aquaticum (Vell.) Verdc.", "TaxonKey is Oenothera oakesiana (A.Gray) J.W.Robbins ex S.Watson", "TaxonKey is Oenothera curtiflora W.L.Wagner & Hoch", "TaxonKey is Fuchsia parviflora Lindl.", "TaxonKey is Sciurus carolinensis Gmelin, 1788", "TaxonKey is Anthyllis montana L.", "TaxonKey is Oenothera ×wratislaviensis Rostanski", "TaxonKey is Sciurus niger Linnaeus, 1758", "TaxonKey is Oenothera royfraseri R.R.Gates", "TaxonKey is Oenothera elata Kunth", "TaxonKey is Pontederia cordata L.", "TaxonKey is Oenothera rosea Aiton", "TaxonKey is Myocastor coypus (Molina, 1782)", "TaxonKey is Oenothera stricta Link", "TaxonKey is Oenothera ×oehlkersii Kappus", "TaxonKey is Oenothera lindheimeri (Engelm. & A.Gray) W.L.Wagner & Hoch", "TaxonKey is Oenothera deflexa R.R.Gates", "TaxonKey is Oenothera fruticosa subsp. glauca (Michx.) Straley", "TaxonKey is Threskiornis aethiopicus (Latham, 1790)", "TaxonKey is Oenothera ×issleri Renner ex Rostanski", "TaxonKey is Pennisetum setaceum (Forssk.) Chiov.", "TaxonKey is Procambarus clarkii (Girard, 1852)", "TaxonKey is Neovison vison (Schreber, 1777)", "TaxonKey is Nasua nasua (Linnaeus, 1766)", "TaxonKey is Orconectes virilis (Hagen, 1870)", "TaxonKey is Oenothera depressa Greene", "TaxonKey is Perccottus glenii Dybowski, 1877", "TaxonKey is Vespa velutina Lepeletier, 1836", "TaxonKey is Oenothera laciniata Hill", "TaxonKey is Spiraea salicifolia L.", "TaxonKey is Tamias sibiricus (Laxmann, 1769)", "TaxonKey is Sicyos angulatus L.", "TaxonKey is Oenothera ×rubricaulis Kleb.", "TaxonKey is Parthenocissus tricuspidata (Siebold & Zucc.) Planch.", "TaxonKey is Trachemys scripta (Thunberg In Schoepff, 1792)", "TaxonKey is Euthamia graminifolia (L.) Nutt.", "TaxonKey is Oenothera ×cambrica Rostanski", "TaxonKey is Myriophyllum heterophyllum Michx.", "TaxonKey is Truellum perfoliatum (L.) Soják", "TaxonKey is Spiraea tomentosa L.", "TaxonKey is Ondatra zibethicus (Linnaeus, 1766)" ] }, "Country is Belgium" ] } The dataset includes 24869 records from 41 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0061072-160910150852091/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences